2013
DOI: 10.1186/1471-2458-13-450
|View full text |Cite
|
Sign up to set email alerts
|

Reasons for poor adherence to antiretroviral therapy postnatally in HIV-1 infected women treated for their own health: experiences from the Mitra Plus study in Tanzania

Abstract: BackgroundIn a study of prevention of mother-to-child transmission of HIV (PMTCT) by triple antiretroviral therapy (ART) in Dar es Salaam, Tanzania (the Mitra Plus study), retrospective viral load testing revealed a high and increasing frequency of detectable viral load during follow-up for two years postnatally in women given continuous ART for their own health suggesting poor adherence. This study explored women’s own perceived barriers to adherence to ART post-delivery so as to identify ways to facilitate b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
117
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(133 citation statements)
references
References 26 publications
9
117
1
6
Order By: Relevance
“…This prevalence is lower than that found by Ngarina et al [12] in Lubumbashi (4.15%), Ndege et al [13] in Kenya (3.3%), Gamell et al [14] in Tanzania (2.6%), Musarandega et al [15] in Zimbabwe (16.3%) and Tenthani et al [16] in Malawi (12.8%). The impact of HIV/AIDS observed could explain the discrepancy in these countries.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…This prevalence is lower than that found by Ngarina et al [12] in Lubumbashi (4.15%), Ndege et al [13] in Kenya (3.3%), Gamell et al [14] in Tanzania (2.6%), Musarandega et al [15] in Zimbabwe (16.3%) and Tenthani et al [16] in Malawi (12.8%). The impact of HIV/AIDS observed could explain the discrepancy in these countries.…”
Section: Discussioncontrasting
confidence: 53%
“…From these results, we find that almost 50% of pregnant women who receiving antenatal care have not been screened, which would contribute to an increase in the proportion of pregnant women giving birth with an unknown HIV serological status. Some authors have noted factors explaining this finding, namely the lack of education and information among pregnant women, fear of stigmatization and potential marital collapse; absence or poor involvement of the partner to the program, the conduct of the PMTCT program that doesn't allow clinical management in a humanizing manner [10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…The size and smell of the tablets, taking the medication without an assurance of a meal, and the anticipated side effects are some of the reasons mothers stopped taking the ARVs, hence selfcensoring themselves from coming to the clinic. Studies have also shown that poor adherence to drugs is attributed to the feared side effects [15] and food insecurity [16,17]. Health Education coupled with initial and ongoing HIV and adherence counseling especially with the help of peers will help dispel the myths that are associated with the taking of medication.…”
Section: Discussionmentioning
confidence: 99%
“…Patient-level barriers to ART initiation are often similar to adherence barriers and include denial of the need to start treatment, lack of motivation to stay on treatment, fear of side effects, lack of social support, stigma, fear of disclosure, and the perception that starting ART signifies AIDS and impending mortality. 41,[46][47][48][49][50][51][52] Lower mental health scores were the only psychosocial variable significantly associated with poor adherence in a randomized trial of ART for HIV-1 prevention (HPTN 052). 53 These factors may influence adherence during the initial period after ART initiation, as well as subsequent virologic outcomes.…”
Section: Discussionmentioning
confidence: 99%